RELIABILITY, AVAILABILITY AND MAINTAINABILITY (RAM) ANALYSIS AND THE DEVELOPMENT OF COGENERATION PLANT RELIABILITY BLOCK DIAGRAM (RBD) - MUSA, NURUL FERLIENA (IRC, 2021)
Cogeneration Plants are energy systems that simultaneously generate both useful heat and electricity to power facilities and its systems.